Analisis Kesalahan Penggunaan Modalitas Epistemik Kamoshiremasen, Darou, dan Tabun Pada Mahasiswa Tingkat III Prodi Pendidikan Bahasa Jepang Universitas Riau - Faizah, Fadilah; Aibonotika, Arza; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis research is about the use of [kamoshiremasen] [darou] and [tabun] as epistemic modality. The data this research a gathere by means of questionarys which distributed to third the student of japanese education, education faculty Riau University. This research applaid is descriftiv methode and the main teorys are modality and error analisis.The result of this study indicates that [kamoshiremasen] [darou] and [tabun] are modality that a count for possibility based on logical conclusion from rational theorem. The data in the cates that 60% or most of third year student of the japanese education study program, Riau University tend to more fully understand the leksikal meaning than syntaxtical paterns of [kamoshiremasen] [darou] and [tabun],Keyword: modality, kamoshiremasen, darou, and tabun